CLINICAL FEATURES OF CORNEAL LESIONS IN MICROSPORIDIAL KERATOCONJUNCTIVITIS (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the morphological characteristics of corneal lesions in patients with microsporidial keratoconjunctivitis according to with the Mohanty classification (2021) and to examine related clinical factors.Subjects and methods: A cross-sectional descriptive study was performed on 46 eyes of 41 patients with a confirmed diagnosis of microsporidial keratoconjunctivitis, validated by Gram staining of corneal epithelial scrapings, at the Vietnam National Eye Hospital from January 2025 to August 2025. Corneal lesions were classified based on the system suggested by Mohanty et al. All patients underwent medical treatment comprising 0.02% Chlorhexidine in conjunction with a topical Fluoroquinolone.Results: The average age was 47.9 ± 17.3 years, and 73.2% of the group was female. The average time between the start of symptoms and the first visit was 11.5 ± 10.8 days. A history of agricultural trauma or exposure to mud and soil was noted in 39% of patients, whereas 14.6% had previously received topical corticosteroids before a definitive diagnosis. Corneal involvement displayed significant morphological variability: type 1 lesions (coarse, raised punctate epitheliopathy) were the most common, with subtypes 1b (23.9%) and 1c (23.9%) making up the largest groups. Type 1d (diffuse pattern) made up 13% of cases and was always linked to severe conjunctival hyperaemia (100%). Type 3 lesions (flat punctate epitheliopathy) were also seen a lot (26.1%). The average time to clinical resolution was 18.1 ± 9.4 days, and 47.8% of eyes had a best-corrected visual acuity better than 20/30 after treatment. Residual corneal scarring manifested in two eyes, both categorised as type 1d.Conclusion: Microsporidial keratoconjunctivitis in Vietnam exhibits a wide array of corneal morphological patterns. Central and paracentral coarse raised punctate lesions (type s 1b-1c), along with flat punctate lesions (type 3), represent the principal phenotypes. Correctly and quickly identifying these morphological traits could help with clinical diagnosis and help with therapeutic monitoring.
Keywords: Microsporidia, keratoconjunctivitis, corneal lesion morphology, Mohanty classification, Chlorhexidine.